Return to play and risk of repeat concussion in collegiate football players: comparative analysis from the NCAA Concussion Study (1999–2001) and CARE Consortium (2014–2017). Issue 2 (29th April 2019) - McCrea, Michael; Broglio, Steven; McAllister, Thomas; Zhou, Wenxian; Zhao, Shi; Katz, Barry; Kudela, Maria; Harezlak, Jaroslaw; Nelson, Lindsay; Meier, Timothy; Marshall, Stephen William; Guskiewicz, Kevin M
Abstract : Objective: We compared data from the National Collegiate Athletic Association (NCAA) Concussion Study (1999–2001) and the NCAA-Department of Defense Concussion Assessment, Research and Education (CARE) Consortium (2014–2017) to examine how clinical management, return to play (RTP) and risk of repeat concussion in collegiate football players have changed over the past 15 years. Methods: We analysed data on reported duration of symptoms, symptom-free waiting period (SFWP), RTP and occurrence of within-season repeat concussion in collegiate football players with diagnosed concussion from the NCAA Study (n=184) and CARE (n=701). Results: CARE athletes had significantly longer symptom duration (CARE median=5.92 days, IQR=3.02–9.98 days; NCAA median=2.00 days, IQR=1.00–4.00 days), SFWP (CARE median=6.00 days, IQR=3.49–9.00 days; NCAA median=0.98 days, IQR=0.00–4.00 days) and RTP (CARE median=12.23 days, IQR=8.04–18.92 days; NCAA median=3.00 days, IQR=1.00–8.00 days) than NCAA Study athletes (all p<0.0001). In CARE, there was only one case of repeat concussion within 10 days of initial injury (3.7% of within-season repeat concussions), whereas 92% of repeat concussions occurred within 10 days in the NCAA Study (p<0.001). The average interval between first and repeat concussion in CARE was 56.41 days, compared with 5.59 days in the NCAA Study (M difference=50.82 days; 95% CI 38.37 to 63.27; p<0.0001). Conclusion: Our findings indicate that concussion in collegiate football is managed more conservatively than 15 years ago. These changes in clinical management appear to have reduced the risk of repetitive concussion during the critical period of cerebral vulnerability after sport-related concussion (SRC). These data support international guidelines recommending additional time for brain recovery before athletes RTP after SRC.